FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PEMILIK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM MEMILIKI NOMOR POKOK WAJIB PAJAK (NPWP) (Survey pada Wajib Pajak Pemilik UMKM yang Terdaftar di KPP Pratama Batu) - Putri, Wike Puspasari; Pusposari, Devi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This reserach aimed to determine the effect of the taxpayers understanding, benefits received by taxpayer, trust in tax authorities and tax socialization toward compliance in the micro, small and medium business owners to have a tax number. The data of this research were taken through the distribution of questionnaires to taxpayers that are specific in micro, small and medium business owners that listed on KPP Pratama Batu. Questionnaires can be used in this research were 73 pieces. In this research, researchers used multiple linear regression analysis to test the data research. The results showed that the significant value of the taxpayer understanding variable is 0.012, the benefits received by the taxpayer is 0.010, trust in the tax authorities is 0.024 and tax socialization is 0.036. It shows that understanding the taxpayer, benefits received by the taxpayer, trust in the tax authorities and the tax socialization have positive effect on compliance in the micro,small and medium bsiness owners to have a tax number. Keywords: Taxpayers Understanding, Benefits Received by Taxpayer, Trust in Tax Authorities, Tax Socialization, Compliance in The Micro, Small and Medium Business Owners to Have a Tax Number